Marital Attachment, Conflict Management, and Marital Satisfaction Among Middle-Aged Couples - Mirza Aerunissa; Diah Krisnatuti (Journal of Child, Family, and Consumer Studies, 2025)
Marital satisfaction is the primary goal of a marriage and can be influenced by marital attachment and conflict management. This study aims to analyze the influence of marital attachment and family conflict management on marital satisfaction among middle-aged couples. Data were collected using purposive sampling, involving wives from intact families aged 40–59 years, with adolescent children or from empty nest families. The study was conducted in Lowokwaru Subdistrict, Malang City, involving 66 wives with an average age of 45.97 years. More than three-quarters of the wives from families with adolescent children and empty nest families reported having a secure attachment with their husbands. More than three-quarters of wives from families with adolescent children and more than half from empty nest families demonstrated a moderate level of conflict management. In terms of marital satisfaction, nearly half of the wives from families with adolescent children were categorized as having high satisfaction, while more than half of the wives from empty nest families were in the moderate category. Secure attachment and conflict management were found to have a significant positive relationship with marital satisfaction. Regression analysis showed that longer marital duration, being a family with adolescent children, and effective conflict management had a significant positive effect, while the husband’s age and the wife's employment status had a significant negative effect on marital satisfaction. Younger husbands, longer marital duration, unemployed wives, effective conflict management, and being a family with adolescent children were associated with increased marital satisfaction. Middle-aged husbands and wives are encouraged to actively express care and affection toward each other. Future studies are expected to further examine marital attachment variables and include husbands as research subjects.